2017
DOI: 10.1002/jcb.25719
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impact on Intestinal Stem Cell Functions in Mucosal Homeostasis and Tumorigenesis

Abstract: Multiple cell compartments at or near the base of the intestinal crypt have been identified as contributing intestinal stem cells for homeostasis of the rapidly turning over intestinal mucosa and cells that can initiate tumor development upon appropriate genetic changes. There is a strong literature establishing the importance of the frequently dividing Lgr5+ crypt base columnar cells as the fundamental cell in providing these stem cell-associated functions, but there are also clear data that more quiescent ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 83 publications
1
15
0
Order By: Relevance
“…For example, a purified mouse diet that provides common nutrients at the level of each equivalent to that in humans that is linked to high incidence of human colon cancer causes mouse intestinal tumors and has pronounced effects on which and how mouse intestinal stem cells function. This established that intestinal stem/ progenitor-like cell function can be recruited by the nutritional environment, not only by damage or genetic manipulation of Lgr5 hi cells (Augenlicht, 2017;Li et al, 2019Li et al, , 2020Peregrina et al, 2015). This has important implications for how intestinal homeostasis is maintained in humans where nutrient exposures vary among populations and vary for individuals daily.…”
mentioning
confidence: 99%
“…For example, a purified mouse diet that provides common nutrients at the level of each equivalent to that in humans that is linked to high incidence of human colon cancer causes mouse intestinal tumors and has pronounced effects on which and how mouse intestinal stem cells function. This established that intestinal stem/ progenitor-like cell function can be recruited by the nutritional environment, not only by damage or genetic manipulation of Lgr5 hi cells (Augenlicht, 2017;Li et al, 2019Li et al, , 2020Peregrina et al, 2015). This has important implications for how intestinal homeostasis is maintained in humans where nutrient exposures vary among populations and vary for individuals daily.…”
mentioning
confidence: 99%
“…It has been proposed that cancer development is an inevitable consequence of multiple stem cell divisions and stochastic processes that provoke DNA damage, increasing the probability for tumorigenesis ( 43 ). However, an extensive body of evidence has strongly implicated environmental and other lifestyle factors as significant modulators of cancer risk, including colon cancer ( 44 ). Obesity has proven to be particularly hazardous for cancer risk at many sites, as well as accelerated disease progression and related mortality ( 2 , 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…As occurs in colon tissue [ 134 ], 1,25(OH) 2 D 3 upregulates LGR5 , LRIG1 , SMOC2 and MSI1 stemness genes and downregulates the differentiation genes MUC2 and TFF2 in normal rectum organoids, but not in rectal tumor organoids, which indicates a homeostatic action of 1,25(OH) 2 D 3 on the normal stem cell population in both intestinal areas (colon and rectum) [ 135 ]. Accordingly, studies by Augenlicht’s group have revealed that feeding mice with a low vitamin D 3 and calcium diet or specific-inactivation of Vdr in Lgr5 + intestinal stem cells compromises stem cell properties and function, and thus alters the maturation of Lgr5 + progeny and intestinal homeostasis [ 136 , 137 , 138 ]. Interestingly, in human colon carcinoma cell lines, the miR-372/373 cluster, which is upregulated by the Wnt/β-catenin pathway and enhances stemness, has been found to downregulate VDR RNA and a panel of differentiation genes [ 139 ].…”
Section: Effects Of 125(oh) 2 D 3 mentioning
confidence: 99%